A Value-Driven Approach to Software Project Prioritization: Integrating AHP and Value-Focused Thinking in a Messaging Service Firm - Ningsih, Fauziah Firlita; Wasesa, Meditya (International Journal of Advances in Data and Information Systems, 2025)
As requests for development projects grow, a real-life messaging service firm faces increasing challenges in objectively prioritizing initiatives due to limited developer capacity and a high number of concurrent projects. These issues have resulted in inefficient resource allocation, delayed timelines, and declining customer satisfaction, exacerbated by unclear and unstructured project selection methods. This study proposes an integrated decision-making framework that combines the Analytical Hierarchy Process (AHP), stakeholder analysis, and Value-Focused Thinking (VFT) to address the firm’s prioritization challenges. AHP structures the decision criteria and evaluates project alternatives based on their relative importance, stakeholder analysis identifies key decision-makers and their influence, and VFT ensures alignment with organizational values and strategic goals. To uncover underlying issues and stakeholder expectations, the study employs Problem Tree Analysis, structured interviews, and questionnaires. Four typical sub-project alternatives—Custom Projects, New Features, Bug Fixing, and Optimization—are assessed against four criteria: Cost, Quality, Functionality, and Client Satisfaction. The study concludes with an implementation roadmap and actionable recommendations to improve the firm’s project selection and prioritization process.